Feasibility and Economical Returns from Harar Cultivation - Singh, Samanpreet; Sharma, Kamal; Bhatia, Avinash Kumar; Chaudhary, Nancy (International Journal of Economic Plants, 2021)
For exploring the feasibility of Harar cultivation in lower Himachal, economic analysis was carried out in College of Horticulture and Forestry, Experimental Farm at Khaggal-Neri to computing the total cost of production; Fixed (Land value, Machinery, Implements and Deprecation) and variable (Cost and inputs like FYM, fertilizer, plant material, labour, etc.) and total returns realized from 5th year onward. Grafted Harar cultivation could be a possible alternate to crop diversification especially in frost prone and monkey affected areas. The cost of establishment, benefit-cost ratio, and net returns is determined to analyze the economic feasibility of investment in grafted Harar cultivation. Benefit:cost ratios were computed for different years. The total fixed cost and overall cost of establishment were found out as INR 25,412.70 and INR 69,081.90, respectively. Returns from the fifth year were INR 9,600.00 whereas, the total returns realized up to tenth year were INR 2,02,100.00. Total net returns over total cost and variable cost were INR 1,33,018.10 and INR 1,58,430.80, respectively. B:C ratio worked out for fifth year was 1.41 and 2.93 for the tenth year. The cost of production, net returns and benefit:cost ratio clearly revealed that grafted Harar cultivation is a successful venture. Investment in grafted Harar seems to be stable and viable option for farmers to earn better returns.